Decisão entre dívida local e intercompany loan de multinacionais agrícolas no Brasil - Guimarães, Marcela de Freitas (2022)
of this dissertation is to analyze the drivers that influence subsidiaries of international companies that operate in the Brazilian agricultural market in decision-making on the composition of third-party debt. Using the multiple-case method, we examined five leaders in the Brazilian agrochemical market –agricultural multinationals of different nationalities with subsidiaries in Brazil and interviewed the CFOs and/or treasurers of the respective companies. The evidence found suggests a hierarchy among the proposed hypothesis, where the variable Financing Theory has a greater impact on the debt decision, followed by the Tax variable, which influences with less relevance in decision making, being cited by the interviewees who reinforced the concern with the financial cost. For all respondents, the Country Risk variable is not relevant in the decision-making process since Brazil is extremely relevant for agribusiness and country risk is considered inherent to business. The findings reinforce previous research like Desail et al (2004) and Aggarval and Kyaw (2008) that found similar evidence that countries where external loans are expensive, borrow less from unrelated parties, giving preference to intercompany loans.